OVERUSE INJURY RISK INCREASES WITH YEAR-ROUND SPORT PARTICIPATION IN MIDDLE SCHOOL AGED ATHLETES. Issue 3 (31st March 2019) - Biese, Kevin M.; Post, Eric G.; Schaefer, Dan; Kliethermes, Stephanie; Brooks, Alison; McGuine, Timothy A.; Bell, David
BACKGROUND: Retrospective studies of high school aged athletes have demonstrated that participating in one sport for more than 8 months of the year is a risk factor for overuse musculoskeletal injuries. This research has driven the recommendation that suggests youth athletes should not play a single organized sport for more than 8 months out of the year. However, these recommendations have never been prospectively examined in middle school aged athletes. The purpose of this study is to determine if year-round participation, operationally defined as participating in one sport for more than 8 months of the year, is associated with increased risk of overuse injuries in middle school aged athletes. METHODS: A total of 281 children (female N= 113, 40.2%, age= 12.1±1.2 years; range 10-14 years of age) completed an anonymous online survey with their parents for 39 weeks. A baseline survey was conducted in the first week of September 2017 and then weekly surveys were completed until June 2018. The baseline survey consisted of demographic information, previous injury history, and sport participation volume (months per year in primary sport). The weekly surveys asked participants to report their sleep habits, musculoskeletal injuries, and illnesses. Parents and children were asked to complete the surveys together. Participants were included in the analysis if they completed at least 80% of the total surveys. In the baseline survey, participants identified the previous months for which they played their primary sport. Those who marked more than 8 months out of the past 12 months were classified as "year-round participants." Logistic regression was used to determine if year-round participation (>8 months/year) was a significant predictor of overuse musculoskeletal injuries during the study period. A second logistic regression model was created using the participant's total reported months participating in a single sport as a predictor of overuse injuries. RESULTS: 80 (28.5%) participants were identified as participating year-round in a single sport and 49 overuse injuries were reported during the study period. Athletes who participated in a single sport year-round were more than twice as likely to sustain an overuse injury during the study period compared to non-year-round athletes (OR [95%CI]: 2.20[1.10-4.39], p=0.025), even after adjusting for sex, age, and previous injury history. The odds of sustaining an overuse injury increased approximately 17% for every additional month of participating in a single sport (OR [95%CI]: 1.17 [1.04 -1.32], p=0.012) again while controlling for sex, age, and previous injury. CONCLUSION: This is the first prospective study in middle school aged athletes examining year-round participation and overuse musculoskeletal injuries. Middle school aged athletes are at a 2-times increased risk of overuse musculoskeletal injuries when participating in a single sport for more than 8 months of the year compared to middle school aged athletes who participated 8 or less months in a single sport. Sport specialization has been identified as a risk factor for high school aged athletes for overuse injury – and our observations indicate that a similar trend may exist in middle school aged athletes. Recommendations regarding monthly sport participation for adolescents have been supported in the high school aged population and these recommendations may extend to an even younger population.